Starting the engine of the powerhouse: mitochondrial transcription and beyond - Miranda, Maria; Bonekamp, Nina A.; Kühl, Inge (Biological chemistry, 2022)
Mitochondria are central hubs for cellular metabolism, coordinating a variety of metabolic reactions crucial for human health. Mitochondria provide most of the cellular energy via their oxidative phosphorylation (OXPHOS) system, which requires the coordinated expression of genes encoded by both the nuclear (nDNA) and mitochondrial genomes (mtDNA). Transcription of mtDNA is not only essential for the biogenesis of the OXPHOS system, but also generates RNA primers necessary to initiate mtDNA replication. Like the prokaryotic system, mitochondria have no membrane-based compartmentalization to separate the different steps of mtDNA maintenance and expression and depend entirely on nDNA-encoded factors imported into the organelle. Our understanding of mitochondrial transcription in mammalian cells has largely progressed, but the mechanisms regulating mtDNA gene expression are still poorly understood despite their profound importance for human disease. Here, we review mechanisms of mitochondrial gene expression with a focus on the recent findings in the field of mammalian mtDNA transcription and disease phenotypes caused by defects in proteins involved in this process.
Gesehen am 12.12.2023